Transparent and Participatory Village Fund Management in the Perspective of Local Values and Wisdom of the Kerekeh Village Community, Sumbawa Regency - S., Khairuddin; Maryunani; Badriyah, Nurul (Global Writing Academica Researching & Publishing, 2024)
Accumulatively, the amount of village funds budgeted to villages continues to increase from year to year. However, the fact is that there are still many villages that have not been able to utilize the presence of village funds optimally. Low community participation in managing village funds is one of the important factors hindering village development. This research has several objectives, namely first, to see what transparent and participatory village fund management looks like in Kerekeh village. Second, explore the local wisdom values ​​of the Kerekeh village community. This research is qualitative descriptive research using a phenomenological approach. Research data was obtained from the results of in-depth interviews with research informants and direct observation at the research location. The data that has been obtained is then processed and analyzed through three stages, namely data reduction, data presentation and drawing conclusions. The research results show that (1) The Kerekeh village government has attempted to provide opportunities for the community to participate in every village fund management process. The village government also provides access and opportunities for village communities to obtain information related to village fund management by providing information channels containing various village activities and programs funded using village funds, such as websites and village information boards. (2) There are traditions that are still maintained and held firmly by the Kerekeh village community, such as tokal-adat, laong-pantar and basiru which require local wisdom values ​​such as a sense of family, honesty, trust and a spirit of togetherness.